PROCESS OPTIMISATION AND QUALITY EVALUATION OF INSTANT CUSTARD POWDER INCORPORATED WITH RESISTANT STARCH FROM GRAND NAINE BANANA - SRUTHY. P. M; SHARON. C. L; SEEJA THOMACHAN; A. N. JYOTHI; ANEENA E. R (The Journal of Research ANGRAU, 2025)
The research aimed (2023-2024) to create an instant custard powder utilizing resistant starch derived from the Grand Naine banana.The process involved peeling, slicing, drying, and powdering mature banana at 50!, followed by isolating starch from banana flour using a modified water-alkaline extraction method. Isolated starch was modified by autoclaving at 121! for 30 minutes with a moisture content of 10 per cent. Custard powder was prepared by incorporating resistant starch at different levels with corn flour and other suitable ingredients (T0- T6 ). Custard were formulated using these treatments and subjected to organoleptic evaluation. The most effective treatment was selected through sensory evaluation using a scorecard with a nine-point hedonic scale. The maximum score for all the organoleptic attributes was obtained for custard (T4), which were prepared by blending resistant starch (20 %), corn flour (15 %) and other ingredients (65 %). The nutritional composition of the selected custard powder included moisture (6.25 %) carbohydrate (63.64 g 100g-1), starch (54.95 %), resistant starch (14.64 %) and in vitro digestibility of starch (45.2 %). The formulated custard powder containing banana resistant starch resulted in slowly digestible starch characteristics, accomplishing this without significantly affecting the sensory qualities.